Flotation Sludges from Precious Metal Recovery Processes: From Waste to Secondary Raw Material in Ceramics - Matteo Perotti; Francesco Iacoviello; Narcisa M. Marian; Carlo Indelicato; Giancarlo Capitani; Riccardo Salvini; Marco Zampini; Cecilia Viti (Recycling, 2023)
In this study, we investigated flotation muds (FM) deriving from the recovery processes of precious metals contained in e-waste (wastes from electronics) and exhausted catalysts. FM consist of an amorphous phase, corresponding to a Ca- and Al-rich silicatic glass, potentially usable as a secondary raw material (SRM) to obtain a final ceramic product (CFM). A high FM amount was used in our ceramic tests, and suitably mixed with variable percentages of other phases. Chemical analysis, phase composition, microstructure, pore pattern and technological properties of the new ceramic products were determined using different analytical techniques, including bulk XRF, XRD, SEM-EDS and µCT. The CFM product predominantly consists of nepheline, pyroxene and wollastonite as the main crystalline phases, with a minor amorphous phase occurring as a compact interstitial matrix. The ceramic product has a porous interconnected microstructure. Nevertheless, this microstructure does not negatively affect the mechanical properties of the ceramic product, as testified by the geo-mechanical tests, revealing good properties in terms of bending and uniaxial strength. These preliminary results point out that FM recycling is feasible, at least at the laboratory scale.